2019
DOI: 10.1002/ccr3.2429
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term survival after surgery of pancreatic primary squamous cell carcinoma: A case report and literature review

Abstract: Pancreatic primary squamous cell carcinoma is rarer and no optimal treatment has been validated according to the tumor stage. The surgical resection was the only curative option. The radiotherapy or chemotherapy was performed for the other cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 47 publications
(55 reference statements)
1
9
0
Order By: Relevance
“…The stereotype of patient diagnosed with primary pancreatic carcinomas with squamous component is, like our cases, a male in his 6 th decade of life showing an infiltrative tumor of the head of the pancreas [9,10].…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The stereotype of patient diagnosed with primary pancreatic carcinomas with squamous component is, like our cases, a male in his 6 th decade of life showing an infiltrative tumor of the head of the pancreas [9,10].…”
Section: Discussionsupporting
confidence: 51%
“…[1,3,[6][7][8]17,22]. Although nabpaclitaxel seems to be superior to platinum salts ones [10], it is not reimbursed in medium-income countries and gemcitabile is the therapy of choice in such cases. Immunotherapy might be the election choice in cases with high PD-L1 expression [17].…”
Section: Discussionmentioning
confidence: 99%
“…However, the standard care for the metastatic setting is still lacking ( 9 , 10 ). Data from sporadic reports revealed that 38.5% of metastatic patients received palliative care, and others commonly underwent a combination of cisplatin and 5‐fluorouracil or gemcitabine, showing a short median OS of 4 months, compared with 17 months in the resectable group and 8 months in the locally advanced tumor group ( 11 ). A pool of data regarding pancreatic SCC available in the public domain showed a median OS of 7 months in 54 patients with pancreatic SCC, and resectable cases had significantly better OS when compared with non-resectable cases (10 months versus 4 months, respectively) ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…reported a case of a locally advanced SCC of the pancreatic tail showing an OS of 1 year following treatment with an albumin-free nanosomal paclitaxel lipid suspension-based regimen ( 13 ). A recent study described a patient with T2N0M0R0 primary SCC of the pancreas, who received chemotherapy of gemcitabine following surgery and achieved a long relapse-free survival of 26 months ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…As per the other types of PC, surgical resection is the only curative approach for ASPC and SCC , that can significantly improve survival[ 107 , 110 , 119 , 120 ]. Patients affected by ASPC or SCC undergoing surgery and post-operative treatment with chemotherapy, radiotherapy or both appear to have a benefit[ 108 , 121 - 123 ], even though there is no consensus regarding the best regimen to use, that are commonly fluoropyrimidine-based, gemcitabine based or platinum-based.…”
Section: Adenosquamous Carcinoma and Squamous Cell Pancreatic Carcinomentioning
confidence: 99%